The virtual contention window concept for modeling processes on ad-hoc IEEE 802.11 networks - Lazebnyy, Volodymyr; Lazebnyy, Anton; Meleshko, Mykola (Видавництво Львівської політехніки, 2012)
The concept of virtual contention window is offered for competitive evaluation process in a wireless network that operates at IEEE 802.11 standard in a saturated mode. The concept allows to obtain the functional dependence for a single station, and to segment the wireless network as a whole.
Keywords: WLAN; virtual contention window; IEEE 802.11; wireless; network